Science in wonderland : the scientific fairy tales of Victorian Britain - Keene, Melanie (Oxford University Press, 2015)
In Victorian Britain an array of writers captured the excitement of new scientific discoveries, and enticed young readers and listeners into learning their secrets, by converting introductory explanations into quirky, charming, and imaginative fairy-tales; forces could be fairies, dinosaurs could be dragons, and looking closely at a drop of water revealed a soup of monsters. Science in Wonderland explores how these stories were presented and read. Melanie Keene introduces and analyses a range of Victorian scientific fairy-tales, from nursery classics such as The Water-Babies to the little-known.